Authentication of Silybum marianum Varieties Using RAPD Analysis (Plant Tissue Culture and Biotechnology, 2014)
Silybum marianum is an important medicinal plant used for hepatic disorders. Two varieties exist for this plant S. marianum var. album (white-flowered) and S. marianum var. purple (purple-flowered). A fast and simple method (RAPD) was developed for authentication of S. marianum varieties (purple- and white- flowered) at a DNA level. The two varieties were distinguished by polymorphic bands generated by four decamer primers, namely, OPP-10, OPG-03, OPG-01, and OPC-17. The developed RAPD method will be useful for practical authentication of S. marianum varieties and their adulterants. Plant Tissue Cult. & Biotech. 24(1): 57-63, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19200